EFEKTIVITAS METODE CRH BERBANTUAN PjBL DALAM MENINGKATKAN PEMAHAMAN AUTOCAD DAN HASIL BELAJAR KONSTRUKSI UTILITAS GEDUNG - Dea Nisfuha Anindya; Fadila Fitria Wulandari; Ahmad Yudi Mubarroq (LPPM Universitas Negeri Jakarta, 2026)
The study aims to identify how effective the application of the Course Review Horay (CRH) method assisted by Project Based Learning (PjBL) is in optimizing students' understanding of AutoCAD and student learning outcomes. This research uses a quantitative approach with a quasi-experimental type. Covering two sequences with four main procedures namely design, action, observation, and reflection. The population in this study is all students of class XI DPIB SMK Negeri 1 Kemlagi which includes 3 classes totaling 99 people. The sample was selected as many as 66 people using purposive sampling technique, namely class XI DPIB 2 as the experimental class and class XI DPIB 3 as the control class. Data were collected through observation, tests, and documentation. Item analysis using t test and obtained the value of learning outcomes Sig. 0.000 <0.005, meaning that learning methods have an influence on student learning outcomes. The correlation coefficient obtained an R Square score of 0.960, while N-Gain testing produced an average of 0.5245 or 52.45%, proving that the implementation of learning methods can optimize student learning outcomes effectively. The findings of this study prove that the Course Review Horay method is effective in optimizing students' understanding and learning achievement of AutoCAD.